Community of practice i indywidualizacja w nauczaniu - Małgorzata Karwowska-Struczyk (Problemy Wczesnej Edukacji)
Community of practice and the individualization of the educational process are the central concepts of the author’s reflections. In the article, selected conceptualizations of the community of practice have been presented. They have been found to be a starting point for the individualization of the educational approach to children at preschool and school age. The importance of the involvement of the whole local community in creating the educational environment has been shown on a basis of two ready for use models of community of practice proposed by P. Moss and R. Myers. The concept of individualization has been considered in the second part of the text. In this respect, self-esteem, as the major factor of the personalization of the educational dialogue between an adult (teacher) and a child, has been underlined. Its potential strength in determining the effects of the personalized interactions between an adult and a child has been highlighted.